2017
DOI: 10.1186/s13104-017-2903-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of pulmonary hypertension in a group of Cameroonian patients without chronic lung disease: a cross-sectional echocardiographic study

Abstract: ObjectiveTo study prevalence and determinants of pulmonary hypertension (PH) in a group of Cameroonian patients without chronic lung disease. We conducted a cross-sectional study conducted between April and December 2011 in a private cardiology clinic in Bafoussam, Cameroon. We included consenting participants aged ≥ 18, who underwent a Doppler echocardiography. Patients with chronic lung disease were excluded.ResultsA total of 178 participants were enrolled, of whom 44.4% were males with a mean age of 63.1 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…It can be seen from the above results that patients with PH are older patients. In the study by Ahmadou M. Jingi et al, 178 patients were evaluated, and this study indicated that age is a strong predictor of PH [9]. This result was similar to our research.…”
Section: Discussionsupporting
confidence: 91%
“…It can be seen from the above results that patients with PH are older patients. In the study by Ahmadou M. Jingi et al, 178 patients were evaluated, and this study indicated that age is a strong predictor of PH [9]. This result was similar to our research.…”
Section: Discussionsupporting
confidence: 91%